2007
DOI: 10.1097/pas.0b013e31805c9cd9
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Bladder: A Clinicopathologic Analysis of 45 Cases

Abstract: Squamous cell carcinoma of the bladder comprises less than 5% of all bladder cancers in the United States and its long-term prognosis has remained controversial. We examined a large series of patients who underwent radical and partial cystectomies for squamous cell carcinoma to identify associated histopathologic findings and clinical outcomes associated with these tumors. Patient age ranged from 46 to 83 years (average 68.5 y) with a male:female ratio of 3:2. Forty-three patients were white and 2 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
106
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 23 publications
6
106
0
3
Order By: Relevance
“…Squamous cell carcinoma is defined by the presence of intercellular bridges or keratinization and may be present in up to 40% of invasive urothelial carcinomas [63][64][65][66]. It is almost never associated with human papillomavirus infection, with the rare exception of some cases with a basaloid morphology [67,68].…”
Section: Invasive Urothelial Carcinoma With Divergent Differentiationmentioning
confidence: 99%
“…Squamous cell carcinoma is defined by the presence of intercellular bridges or keratinization and may be present in up to 40% of invasive urothelial carcinomas [63][64][65][66]. It is almost never associated with human papillomavirus infection, with the rare exception of some cases with a basaloid morphology [67,68].…”
Section: Invasive Urothelial Carcinoma With Divergent Differentiationmentioning
confidence: 99%
“…These include keratinizing squamous metaplasia, non-invasive squamous lesions, smoking and chronic mucosal irritants such as calculi and indwelling catheters. [4][5][6] In Africa, however, chronic infection with Schistosoma hematobium (bilharziasis) is the most common cause. 4,6 Although these tumors are derived from urothelium, they show pure squamous morphology and at the time of diagnosis have often infiltrated the muscularis propria and are thus associated with a poor clinical outcome.…”
mentioning
confidence: 99%
“…Although these are rare and generally regarded as benign lesions, several studies have shown squamous cell carcinoma arising in the background of condylomata. 11,16,17,35 It is important to note that patients in these studies were either chronically immunosuppressed 11,17 or showed persistent condylomatous infection with 11 or without 16 associated extensive vaginal condylomata. Inverted papillomas of the bladder have also been examined for HPV with variable results.…”
Section: Discussionmentioning
confidence: 98%
“…1 HPV is a small circular double-stranded DNA virus with more than 100 different types described to date. 2 The potential of the virus to cause malignant or benign lesions dictates its classification into low-risk (6,11,40,42, and so on) or high-risk (16,18,31,33,45,51, and so on) types. The prototypical model for carcinogenesis is squamous cell carcinoma of the uterine cervix, in which nearly all such carcinomas are associated with HPV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation